Digital technologies prospects in production control of elevators, flour, cereals and feed production - A. E. Biryulin (Безопасность техногенных и природных систем, 2019)
The reasons of overuse of production capacities at storage and processing of vegetable raw materials are determined. The growth rates of gross output of grain and leguminous crops are considered. Elevators, objects of flour, cereals and feed production are considered as important structural elements of micro and macroeconomics. The paper predicts the application of digital technologies in production control and online monitoring of dangerous and harmful production factors. Ways of implementation of this approach on real production processes, which are, controlled both by the operating organization and by the Supervisory authorities are considered. Accidents and fatal injuries at hazardous production facilities of storage and processing of plant raw materials are considered.